2019
DOI: 10.1016/j.dib.2019.103972
|View full text |Cite
|
Sign up to set email alerts
|

Data on SVCT2 transporter expression and localization in cancer cell lines and tissues

Abstract: The data presented in this article are related to the research paper entitled “Increased expression of mitochondrial sodium-coupled ascorbic acid transporter-2 (mitSVCT2) as a central feature in breast cancer”, available in Free Radical Biology and Medicine Journal [1]. In this article, we examined the SVCT2 transporter expression in various breast cancer cell lines using RT-PCR and Western blot assays. In addition, we analyzed the subcellular localization of SVCT2 by immunofluorescence colocalization assays a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…Therefore, the presence of SVCT2 in breast cancer may act as a predictor for the effectiveness of ascorbate treatment [ 115 ]. SCVT2 was overexpressed in the mitochondria of breast cancer cells, but only marginally presented on the plasma membrane [ 116 ]. Augmented expression of mitochondrial SVCT2 appears to be a common hallmark across all human cancers and might have implications for the survival capacity of cancer cells in pro-oxidant environments [ 116 , 191 ].…”
Section: Ascorbate Transportersmentioning
confidence: 99%
“…Therefore, the presence of SVCT2 in breast cancer may act as a predictor for the effectiveness of ascorbate treatment [ 115 ]. SCVT2 was overexpressed in the mitochondria of breast cancer cells, but only marginally presented on the plasma membrane [ 116 ]. Augmented expression of mitochondrial SVCT2 appears to be a common hallmark across all human cancers and might have implications for the survival capacity of cancer cells in pro-oxidant environments [ 116 , 191 ].…”
Section: Ascorbate Transportersmentioning
confidence: 99%
“…Human breast cancer tissues expressed SVCT2, but were not able to take up AA. This was explained by the fact that this form of SVCT2 was absent from the plasma membrane and expressed in mitochondria of breast cancer cells (78). Augmented expression of the SVCT2 mitochondrial form and mitochondrial sequestration of AA might profoundly alter AA-dependent mechanisms in other subcellular compartments and might represent an adaptation mechanism to the special metabolic features in cancer cells.…”
Section: Vitamin C Compartmentalization: Unifying the Different Diseamentioning
confidence: 99%
“…A comprehensive study on this matter, focused on breast cancer cells mechanisms to acquire vitamin C was recently published (Pena et al, 2019;Roa et al, 2019). This work has shown that most (if not all) of the vitamin C that is capture by breast cancer cells is in the oxidized form.…”
Section: Vitamin C Transport and Compartmentalization In Cancer Cellsmentioning
confidence: 99%